Assessing the precision of machine learning for diagnosing pulmonary arterial hypertension: a systematic review and meta-analysis of diagnostic accuracy studies - Fadilah, Akbar; Putri, Valerinna Yogibuana Swastika; Puling, Imke Maria Del Rosario; Willyanto, Sebastian Emmanuel (Frontiers in Cardiovascular Medicine, 2024)
Introduction Pulmonary arterial hypertension (PAH) is a severe cardiovascular condition characterized by pulmonary vascular remodeling, increased resistance to blood flow, and eventual right heart failure. Right heart catheterization (RHC) is the gold standard diagnostic technique, but due to its invasiveness, it poses risks such as vessel and valve injury. In recent years, machine learning (ML) technologies have offered non-invasive alternatives combined with ML for improving the diagnosis of PAH. Objectives The study aimed to evaluate the diagnostic performance of various methods, such as electrocardiography (ECG), echocardiography, blood biomarkers, microRNA, chest x-ray, clinical codes, computed tomography (CT) scan, and magnetic resonance imaging (MRI), combined with ML in diagnosing PAH. Methods The outcomes of interest included sensitivity, specificity, area under the curve (AUC), positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR). This study employed the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool for quality appraisal and STATA V.12.0 for the meta-analysis. Results A comprehensive search across six databases resulted in 26 articles for examination. Twelve articles were categorized as low-risk, nine as moderate-risk, and five as high-risk. The overall diagnostic performance analysis demonstrated significant findings, with sensitivity at 81% (95% CI = 0.76–0.85, p < 0.001), specificity at 84% (95% CI = 0.77–0.88, p < 0.001), and an AUC of 89% (95% CI = 0.85–0.91). In the subgroup analysis, echocardiography displayed outstanding results, with a sensitivity value of 83% (95% CI = 0.72–0.91), specificity value of 93% (95% CI = 0.89–0.96), PLR value of 12.4 (95% CI = 6.8–22.9), and DOR value of 70 (95% CI = 23–231). ECG demonstrated excellent accuracy performance, with a sensitivity of 82% (95% CI = 0.80–0.84) and a specificity of 82% (95% CI = 0.78–0.84). Moreover, blood biomarkers exhibited the highest NLR value of 0.50 (95% CI = 0.42–0.59). Conclusion The implementation of echocardiography and ECG with ML for diagnosing PAH presents a promising alternative to RHC. This approach shows potential, as it achieves excellent diagnostic parameters, offering hope for more accessible and less invasive diagnostic methods. Systematic Review Registration PROSPERO (CRD42024496569).